2010
DOI: 10.1115/1.4003000
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Investigation of Circumferential Grooves on Compressor Rotor Performance

Abstract: This paper presents numerical and experimental investigations about grooved casing treatment with the help of a high-speed small-scale compressor rotor. First, the numerical investigation seeks to offer a contribution of understanding the working mechanism by which circumferential grooves improve stall margin. It is found that stall margin gain due to the presence of circumferential grooves arises from the suction-injection effect and the near-tip unloading effect. Based on that, the philosophy of design of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…The compressor has been applied to various kinds of casing treatments to test their effects on compressor stability for its tip-critical nature. 4,37 Figure 7 shows the test facility and instrumentation for both the steady-state and dynamic measurements. The shaft speed of a 250 kW DC motor was accelerated by a gearbox up to 15,200 r/min.…”
Section: Test Facility and Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The compressor has been applied to various kinds of casing treatments to test their effects on compressor stability for its tip-critical nature. 4,37 Figure 7 shows the test facility and instrumentation for both the steady-state and dynamic measurements. The shaft speed of a 250 kW DC motor was accelerated by a gearbox up to 15,200 r/min.…”
Section: Test Facility and Instrumentationmentioning
confidence: 99%
“…33%, 53%, and 71% of the design speed. The tested facility and measurement method are discussed in detail in Lu et al, 4 Wang et al, 35 and Wu et al 37 Results and discussion Effect on compressor stability…”
Section: Test Facility and Instrumentationmentioning
confidence: 99%
“…Indeed, numerous attempts have been made to develop tip flow control strategies. They have ranged from active methods, e.g., real-time control of the IGV stagger angle [24] and momentum injection into the casing endwall boundary layer upstream of the rotor [25,26] to passive techniques, such as endwall casing treatments [27,28]. Although it has been established that casing treatments do extend the stall margin, insufficient understanding of the flow mechanisms involved has hindered the ability to, for instance, optimize the location and geometry of grooves.…”
Section: Introductionmentioning
confidence: 98%
“…Several other groups have attempted to explain the effectiveness of circumferential grooves. From the stable flow point of view, Muller [11] and Wu et al [13] suggested that the circumferential grooves delay the overflow at the leading edge of blade tips, thereby enlarging the stall margin. Zhao et al [15] studied the unstable flow effects of the circumferential grooves on the leakage flow at blade tips.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Muller [11] and Raba and Hah [12] suggested that the leading edge of the blade is the best position. Wu Anhui [13] and Bennington [14] reported that the stability extension achieved through circumferential groove treatments decreases as the groove width increases. In addition, Bailey [9] and Bennington [14] reported that the stability extension effect increases with increasing groove depth.…”
Section: Introductionmentioning
confidence: 99%